A qualitative study of sedentary behaviours in stroke survivors: non-participant observations and interviews with stroke service staff in stroke units and community services. Issue 20 (25th September 2022) - Morton, Sarah; Hall, Jennifer; Fitzsimons, Claire; Hall, Jessica; English, Coralie; Forster, Anne; Lawton, Rebecca; Patel, Anita; Mead, Gillian; Clarke, David J.
Abstract: Purpose: Sedentary behaviour (SB) is associated with negative health outcomes and is prevalent post-stroke. This study explored SB after stroke from the perspective of stroke service staff. Methods: Qualitative mixed-methods study. Non-participant observations in two stroke services (England/Scotland) and semi-structured interviews with staff underpinned by the COM-B model of behaviour change. Observations were analysed thematically; interviews were analysed using the Framework approach. Results: One hundred and thirty-two observation hours (October - December 2017), and 31 staff interviewed (January –June 2018). Four themes were identified: (1) Opportunities for staff to support stroke survivors to reduce SB; (2) Physical and psychological capability of staff to support stroke survivors to reduce SB; (3) Motivating factors influencing staff behaviour to support stroke survivors to reduce SB; (4) Staff suggestions for a future intervention to support stroke survivors to reduce SB. Conclusions: Staff are aware of the consequences of prolonged sitting but did not relate to SB. Explicit knowledge of SB was limited. Staff need training to support stroke survivors to reduce SB. Sedentary behaviour in the community was not reported to change markedly, highlighting the need to engage stroke survivors in movement from when capable in hospital, following through to home. Implications for rehabilitation: Stroke survivor sedentary behaviour is influenced, directly and indirectly, by the actions and instructions of stroke service staff in the inpatient and community setting. The built and social environment, both in the inpatient and community settings, may limit opportunities for safe movement and can result in stroke survivors spending more time sedentary. Stroke service staff appreciate the benefit of encouraging stroke survivors to stand and move more, if it is safe for them to do so. Staff would be amenable to encourage stroke survivors to reduce sedentary behaviour, provided they have the knowledge and resources to equip them to support this.